Growth alteration of Allium cepa L. roots exposed to 1.5 mT, 25 Hz pulsed magnetic field - González Vidal, Alejandro; Mercado-Sáenz, Silvia; Burgos-Molina, Antonio Manuel; Sendra-Portero, Francisco; Ruiz-Gómez, Miguel José (Taylor & Francis, 2022)
The response of plants to magnetic fields (MF) is not fully understood. This work studies the effects of pulsed MF on the germination and growth of Allium cepa roots. Onions were exposed to 25Hz, 1.5mT, 33h. Pulsed MF was generated by a Helmholtz-type equipment that generated rectangu-lar voltage pulses. The results showed that fewer roots grew in the speci-mens exposed to pulsed MF (14±6 roots on day 1 to 21±8 on day 4) than in the control groups (32±17 to 48±23) (p<0.05 Friedman). Control speci-mens showed a root mean length of 7±4 mm (day 1) and 24±10 mm (day 4). The specimens treated with pulsed MF showed a length of 4±2 mm (day 1), reaching 18±9 mm on day 4 (p<0.001 ANOVA). In conclusion, the exposure of Allium cepa specimens to 25Hz, 1.5mT pulsed MF during 33h produces a decrease in the germination and growth of roots.
Keywords: Plantas - Crecimiento; Campos magnéticos - Efectos fisiológicos; Pulsed magnetic field; Allium cepa; growth; root; plant